Thermic effect of food and resting energy expenditure following sleeve gastrectomy for weight loss in adolescent females - Brehm, Bonnie (Surg Obes Relat Dis, 2020)
BACKGROUND: Few studies have addressed the effect of bariatric surgery on factors related to energy balance, including resting energy expenditure (REE) and thermic effect of food (TEF). To our knowledge, very few studies have examined changes in REE and none have investigated modifications in TEF after sleeve gastrectomy (SG) performed in adolescents. OBJECTIVE: To assess energy expenditure in females who underwent SG as adolescents and matched control participants as preliminary data about SG’s potential to confer differences in postprandial energy expenditure. SETTING: Children’s Hospital Medical Center, United States METHODS: In this observational study, REE and Respiratory Quotient (RQ) were measured via indirect calorimetry, followed by a standardized meal and assessment of TEF and postprandial RQ. Plasma drawn before and every 15 minutes after the meal was assayed for insulin, glucose and c-peptide. Usual dietary intake was estimated using 24-hour recall interviews. RESULTS: Fasting REE and RQ were similar between surgical and control groups. Post-meal TEF also did not differ between groups. The surgical group had higher RQ early in the postprandial period, whereas the control group’s RQ was higher 125+ minutes post-meal. Compared to the control group, the surgical group had lower postprandial glucose and higher insulin and C-peptide and consumed less daily energy during usual intake. CONCLUSIONS: Post-prandial RQ was consistent with the rapid gastric emptying typical of SG, yet we observed no group differences in REE or TEF. These findings may have been due to limited statistical power. More comprehensive studies of EE following SG are warranted.